Corporate Tax Integrity and the Market Reactions to Covid-19: Evidence from China. Issue 1 (2nd January 2022) - Wang, Pin; Xie, Linlin; Wang, Di
ABSTRACT: We compare the market reactions to the COVID-19 crisis of Chinese listed firms with high versus low tax integrity. We show negative market reactions to the crisis across all firms, which is consistent with investors expecting COVID-19 to negatively impact firms' future prospects. Using tax-paying credit rating as a proxy for tax integrity, we find that the negative reaction to the COVID-19 crisis is significantly less for firms with high tax integrity, consistent with investors expecting tax integrity to benefit firms during the crisis. In contrast, we find no difference in the negative market reactions to the 2003 SARS outbreak for the same set of firms. As there was no tax credit rating disclosure in 2003, this serves as a control for the treatment effect. Overall, our results suggest that investors expect corporate tax integrity to mitigate the negative effect of exogenous crises such as COVID-19 on firms.